PERANCANGAN DATABASE RELATIONAL PADA TOKO BUKU ONLINE - Al Husain; Felita Ariyanti; Sinudarwati Sinudarwati (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
Journal report titled "Designing Database at Online Bookstore" Task Journal report aims to design a database to facilitate the process of buying and selling online for consumers. Besides the new system design is also done with the preparation of the overall system that consists of data normalization, ERD, database file. The methodology of the research is includes field studies and literature. Field studies include observations, interviews. Literature study is being conducted by the research literature relevant to the problem. Once the global design is finished it can be seen that report generation earlier with manual processes by collecting data one by one so that the time allowed is not enough, then the procurement database design report will be easier.